Lithuanian Online News Media Role in the COVID-19 pandemic - Aleksandravičiūtė, Ugnė Kotryna; Dabužinskaitė, Unė; Daškevičiūtė, Adelė; Juozapaitis, Lukas; Mockūnaitė, Milda; Petrikaitė, Reda; Raslanaitė, Gabija; Sąlygaitė, Jonė; Stankevičiūtė, Emilija; Šukauskaitė, Roberta; Vajavudzkaitė, Urtė; Žukauskas, Aurimas (Žurnalistikos tyrimai, 2021)
The World Economic Forum’s (WEF) Strategic Analysis Model outlines areas where the role of the media is important during a pandemic, so these areas may be selected to examine how the Lithuanian media perform their public information function during the COVID-19 pandemic. The study of the content of the Lithuanian media clarifies whether the media take into account the areas that, according to the WEF strategic analysis model, the media has an impact during the COVID-19 outbreak. This should provide new insights into the priorities and communication strategies of the Lithuanian media, especially in the context of the COVID-19 crisis. The aim of the article is to present three Lithuanian online newspapers quantitative and qualitative research and, in the context of the WEF Strategic Analysis model and, based on the data obtained, to assess the role of the Lithuanian media during the COVID-19 pandemic. It has been established that during the pandemic, Lithuanian online media pay sufficient attention to the topic of general governance: good and bad cases of health crisis management are shown to the public. However, during the research it became clear that international news on the topic of global governance dominates in Lithuanian news media: the media pay more attention to events in the international arena, and the challenges of Lithuania‘s internal management account for only a fifth of all information in the researched online newspapers. The article was prepared by Vilnius University journalism master students (2020).
Keywords: COVID-19 Pandemic; World Economic Forum; Media role; global governance; human rights; global health; culture and the arts; Lithuanian online news newspapers; Delfi.lt; 15min.lt; Lrt.lt